SIMULASI DAN VALIDASI MPPT-FUZZY LOGIC PADA WECS SKALA MIKRO UNTUK APLIKASI MEDICAL COLD CHAIN - Lailatul Inayah (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The availability of reliable energy is an important for maintaining the continuity of the medical cold chain, particularly for the storage of vaccines and other medical products that require continuous temperature control. Limited access to electricity and frequent power outages in certain regions highlight the need for sustainable alternative energy sources. This study aims to develop a micro-scale WECS based on a PMSG and a Fuzzy Logic-based MPPT controller to support the energy requirements of medical cold chain systems. The proposed system was modeled and simulated in MATLAB/Simulink and consisted of a wind turbine, a PMSG, a three-phase rectifier, a boost converter, and an MPPT-Fuzzy Logic controller. Wind speed variations were applied as system inputs to evaluate performance in terms of turbine aerodynamic characteristics, power coefficient (),), tip speed ratio (TSR), output power, and energy generation. Model validation was conducted by comparing the simulated output power with the theoretical power of the wind turbine. The simulation results indicate that the turbine achieved a maximum power coefficient of 0.44 at the optimum TSR ( ≈ 6). The MPPT-Fuzzy Logic controller successfully maintained turbine operation near the maximum power point, increasing the generated energy from 0.384 kWh to 0.552 kWh, representing an improvement of 43.75% compared with the system operating without MPPT. However, the system was only able to satisfy 47.9% of the energy demand required by the medical cold chain. These findings demonstrate that the proposed WECS with MPPT-Fuzzy Logic has significant potential as a renewable energy solution for healthcare facilities located in areas with limited access to electricity.